Cycloartane triterpenoids acid from Garcinia eugenifolia - Jong, Vivien Yi Mian; Ee, Gwendoline Cheng Lian; Md. Sukari, Mohd Aspollah; Yap, Taufiq Yun Hin; Khong, Heng Yen (Asian Publication Corporation, 2013)
A study on the roots of Garcinia eugenifolia has resulted in the isolation of one cycloartane triterpenoid acid i.e., magniferolic acid (1). This is a first isolation and report on this compound from Garcinia eugenifolia. Three other triterpenes which are euphadienol (2), β-sitosterol (3) and friedelin (4) were also obtained. Besides this, the ketone (3-hydroxyphenyl)3,4,5- trihydroxyphenyl)methanone (5) and two xanthones, 5,9-dihydroxy-8-methoxy-2,2- dimethyl-7-(3-methylbut-2-enyl)pyrano[3,2-b]xanthen-6(2H)-one (6) and 1,3,6,8-tetrahydroxyxanthone (7) were also obtained from this plant.